SIKAP APARATUR DESA DALAM PENDISTRIBUSIAN BERAS MISKIN (RASKIN) DI DESA KUALA DUA KECAMATAN SUNGAI RAYA KABUPATEN KUBU RAYA - E.21109001, Sapudin (FISIP Universitas Tanjungpura, 2013)
Silvan Apparatus attitude deep distribution Indigent Rice (Raskin) at confluence Village Two Raya River district Raya Fortification Regency, known crowded problem. That problem initially stemmed of effort gets gain politically and also economically of party that has authority its settle. Therefore, research majors on: (1 ) Distribution of Raskin Procedure or mechanism at Silvan confluence Two is gone upon for silvan head policies after generalizations in order to saturated right for indigent society basic rights at silvan that; (2 ) Attitude carry the wind villages with its apparatus that distribution of Raskin is gone upon motif up economy and political orientation; and (3 ) Distribution of Raskin reality ala under investment fairly so gets society comments, notably comment hits coordination and Raskin channelizing procedure that is still crowded weakness. Its weakness indication, as shift of depreciation charge on division Raskin what do progressively add RTM distress, added by its slowness in utilize Society Denunciating Unit (UPM) following processes Raskin denunciating handle.Â Keywords: Procedure, Apparatus attitude, Indigent Rice and Society Comment.Â